A CONSTITUTIONAL HISTORY OF BRAZIL THROUGH DOCTRINE AND THE PRESS: THE RULE OF LAW AND THE HEAT OF THE PRINT - Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research investigates the Brazilian constitutional evolution between 1824 and 1988, exploring the duality between the rule of law and the press narrative of the time. The research problem lies in the permanent tension between doctrinal theory and political practice, questioning how institutional ruptures and restorations were legitimized or challenged within the media. The adopted methodology is qualitative and documentary, based on the intersection of classical legal exegesis and the analysis of primary sources from the National Library’s Digital Newspaper Archive (Hemeroteca Digital). The findings demonstrate that Brazil’s constitutional history is not a static process, but a living organism shaped by the discursive clash between jurists and journalists. It was observed that the stability of the Constitutions depended less on technical rigor and more on the interpretive courage of civil society in the face of arbitrary power. Ultimately, the research reveals that the 1988 “Citizen Constitution” consolidated a historical democratic learning process, establishing human dignity as an indispensable axis to shield the future against the authoritarian oscillations that marked the national trajectory.